2021
DOI: 10.1057/s41262-021-00259-1
|View full text |Cite
|
Sign up to set email alerts
|

Beware, an underdog may bite: literature review and brand management framework in the context of underdog brands

Abstract: An underdog brand is a brand with humble resources that competes with passion and determination against competitors that dominate a market. Numerous anecdotal examples and a few research articles of underdog brands exist, yet the understanding of what an underdog brand is and how brands can use the underdog effect is still limited. Considering the relevance of underdog brand management for practice, the purpose of our article is to distill the components of the concepts “underdog brand” and “the underdog effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Extending the underdog effect Our study revolves around a deeper understanding of the commonly known underdog effect (Schmidt and Steenkamp, 2022), which occurs because of an individual preference for less equipped entities or outsiders. A company's positioning based on an underdog brand story is therefore characterized by humbling beginnings and limited resources but equipped with strong determination and passion.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the underdog effect Our study revolves around a deeper understanding of the commonly known underdog effect (Schmidt and Steenkamp, 2022), which occurs because of an individual preference for less equipped entities or outsiders. A company's positioning based on an underdog brand story is therefore characterized by humbling beginnings and limited resources but equipped with strong determination and passion.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has examined underdog brand in the context of consumer behavior, as seen in studies conducted by McGinnis and Gentry (2009) and Paharia et al (2011), the extent to which brands can leverage the underdog effect remains limited (Schmidt and Steenkamp, 2022). However, less is known about the psychological mechanisms that drive consumers' positive reactions to a brand positioned as an underdog through advertising (Jun et al, 2015).…”
Section: The Effects Of Brand Positioning 459mentioning
confidence: 99%
“…Underdog and top‐dog brands have been well studied in the contexts of brand positioning (He et al, 2020; Li & Zhao, 2018; Schmidt & Steenkamp, 2022; Tang & Tsang, 2020) and communication appeals (Antonetti & Baghi, 2021; Moisio et al, 2021). Tang and Tsang (2020) suggested that many marketers opt to position their brands as underdogs—emphasizing the brand's journey and challenges en route to their current success—because customers can easily identify with the struggles of underdog brands.…”
Section: Theorymentioning
confidence: 99%
“…Thus, a competent conversational style aligns with top‐dog positioning, resulting in high perceived fit and a positive consumer evaluation of the brand. Conversely, a warm conversational style, which may be perceived as weak and indecisive, conflicts with the positioning of a top‐dog brand as an industry leader (Schmidt & Steenkamp, 2022; Tang & Tsang, 2020). Thus, when a top‐dog brand adopts a warm conversational style, its consumers perceive low fit and negatively evaluate the brand.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation